Untangling hotel industry’s inefficiency: an SFA approach applied to a renowned Portuguese hotel chain - Ferreira, N. B.; Oliveira, M.M. (9th International Conference on Computational and Financial EconometricsLondon, UK, 2015)
The present paper explores the technical efficiency of four hotels from Teixeira Duarte Group - a renowned Portuguese hotel chain. An efficiency ranking is established from these four hotel units located in Portugal using Stochastic Frontier Analysis. This methodology allows to discriminate between measurement error and systematic inefficiencies in the estimation process enabling to investigate the main inefficiency causes. Several suggestions concerning efficiency improvement are undertaken for each hotel studied.